Removal of dental implants: review of five different techniques. Issue 5 (May 2016) - Stajčić, Z.; Stojčev Stajčić, L.J.; Kalanović, M.; Đinić, A.; Divekar, N.; Rodić, M.
Abstract: The aims of this study were to review five different explantation techniques for the removal of failing implants and to propose a practical clinical protocol. During a 10-year period, 95 implants were explanted from 81 patients. Explantation techniques used were the bur–forceps (BF), neo bur–elevator–forceps (ηBEF), trephine drill (TD), high torque wrench (HTW), and scalpel–forceps (SF) techniques. The following parameters were analyzed: indications for explanation, site of implantation, and the type, diameter, and length of the implant removed. The most frequent indications for implant removal were peri-implantitis ( n = 37) and crestal bone loss ( n = 48). The posterior maxilla was the most frequent site of implant removal ( n = 48). The longer implants were more frequently removed ( n = 78). The majority of implants were removed after 1 year in function ( n = 69). The BF/ηBEF and SF techniques were found to be the most efficient. Explantation techniques appeared to be successful for the removal of failing implants. The BF/ηBEF and SF techniques demonstrated 100% success. The ηBEF technique enabled safe insertion of a new implant in the same explantation site. The HTW technique appeared to be the most elegant technique with the highest predictability for insertion of another implant. An explantation protocol is proposed.